1998
DOI: 10.1083/jcb.142.4.1121
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Talin Gene Compromises Focal Adhesion Assembly in Undifferentiated but Not Differentiated Embryonic Stem Cells

Abstract: We have used gene disruption to isolate two talin (−/−) ES cell mutants that contain no intact talin. The undifferentiated cells (a) were unable to spread on gelatin or laminin and grew as rounded colonies, although they were able to spread on fibronectin (b) showed reduced adhesion to laminin, but not fibronectin (c) expressed much reduced levels of β1 integrin, although levels of α5 and αV were wild-type (d) were less polarized with increased membrane protrusions compared with a vinculin (−/−) ES cell mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
137
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(156 citation statements)
references
References 66 publications
18
137
0
Order By: Relevance
“…The latter possibility is suggested by biochemical studies of ␤ integrin cytoplasmic tails demonstrating that the Y-A mutation disrupts interaction with the cytoskeletal protein talin (Calderwood et al 2002) and the observation that talin-deficient ES cells lose surface expression of ␤1 integrins (Priddle et al 1998). To address this question, mutant ␤1 integrin expression and function were next studied in homozy- Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The latter possibility is suggested by biochemical studies of ␤ integrin cytoplasmic tails demonstrating that the Y-A mutation disrupts interaction with the cytoskeletal protein talin (Calderwood et al 2002) and the observation that talin-deficient ES cells lose surface expression of ␤1 integrins (Priddle et al 1998). To address this question, mutant ␤1 integrin expression and function were next studied in homozy- Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A small population (<5%) of FlnA-containing platelets could be detected in some animals, suggesting mosaic GATA1-Cre expression, rendering incomplete FlnA loxP excision. Whether these platelets contain full-length FlnA or a truncated form, as shown for talin (Priddle et al, 1998), remains to be investigated. The high efficiency of gene inactivation is similar to that described for the widely used megakaryocytespecific Pf4-Cre transgenic mouse and posits the GATA1-Cre mouse as a strong alternative for studies in megakaryocytes and platelets (Léon et al, 2007;Petrich et al, 2007;Tiedt et al, 2007;Hitchcock et al, 2008;Wen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the downregulation of vinculin in Balb\c 3T3 cells with the use of antisense technology resulted in cells that were less well spread, assembled smaller focal adhesions and were more motile [53], whereas over-expression of vinculin in the same cell line led to the assembly of larger focal adhesions and a lower motility of cells [54]. However, gene disruption studies have shown that, whereas talin is essential to the assembly of focal adhesions in mouse embryonic stem cells, vinculin is not [14]. Neither is vinculin essential for focal adhesion assembly in mouse F9 embryonic carcinoma cells, although the F9 cells were less well spread and showed decreased adhesion to laminin and fibronectin [55].…”
Section: Figure 7 Domain Structure Of Talinmentioning
confidence: 99%
“…Down-regulation of talin expression in HeLa cells slowed down the rate of cell spreading and caused a decrease in the size of focal adhesions [11] ; microinjection of antibodies against talin into fibroblasts led to the disruption of focal adhesions and actin stress fibres [9,12], as did certain talin polypeptides [13]. Finally, mouse embryonic stem cells in which both copies of the talin gene were disrupted showed extensive membrane blebbing, a decrease in cell polarity and an inability to form focal adhesions [14].…”
Section: Introductionmentioning
confidence: 99%